Analysis of the distribution of macronutrients of food baskets delivered by municipalities during the Covid-19 pandemic in Peru - Morales-Cahuancama, Bladimir (2022)
Objectives. Evaluate and compare the macronutrient distribution of the food baskets delivered by Peruvian municipalities during the COVID-19 pandemic according to the geographic domain and assigned budget level. Materials and methods. Secondary analysis of the database “Consultation of Acquisition and distribution of basic necessities of the basic family basket” of the General Comptroller of the Republic. Stratified probability sampling was carried out. The distribution of caloric intake was calculated according to macronutrients and compared with the Acceptable Intervals of Macronutrient Distribution (IADM) of the Institute of Nutrition of Central America and Panama (INCAP) and the National Institute of Civil Defense (INDECI). Results. At the national level, the median caloric intake of proteins was 7.7%; carbohydrates 62.5%; and fats 28.1%. The proportion of municipalities with a protein deficit was 84%; Municipalities with excess carbohydrates ranged from 16.5% (according to INCAP) to 35.9% (according to INDECI), and with excess fat, it was 61.6% (according to INCAP) and 20.2% (according to INDECI). According to INDECI, nationally only 9.2% of municipalities delivered baskets with an adequate distribution of macronutrients; Metropolitan Lima stands out with the highest proportions of adequate baskets, while in the Jungle this percentage was less than 5%. Conclusions. Most of the baskets delivered did not have adequate macronutrient distribution. Especially the baskets of municipalities outside of Metropolitan Lima or that had a smaller budget. Carbohydrates and fats were the nutrients that were included in excess, while proteins were deficient.